A 400 nW single-inductor dual-input–tri-output DC–DC buck–boost converter with maximum power point tracking for indoor photovoltaic energy harvesting - Yu, Guolei (2021)
This paper presents a single-inductor dual-input- tri-output buck-boost (DITOBB) converter that manages energy harvesting, energy storage, and power rail regulation of an indoor remote sensor system. The converter operates in discontinuous conduction mode (DCM) and regulates the outputs with a combination of pulse-skipping modulation (PSM) and constant-ON-time pulse-frequency modulation (PFM). To reduce the quiescent power, all the circuit blocks are turned OFF when the outputs are within regulation, except a system clock generator. A newly designed relaxation oscillator provides the main clock of the system, which requires neither reference voltages nor comparators. The frequency of the system clock doubles or halves based on the states of the sources and outputs following a proposed algorithm. The DITOBB converter has been designed and fabricated using 0.18 μm CMOS process. With a quiescent power of 400 nW, the designed DITOBB converter shows a measured peak efficiency of 83% at 100 μW output power.